C⁎-Algebra-Valued G-Metric Spaces and Related Fixed-Point Theorems - Congcong Shen; Lining Jiang; Zhenhua Ma (Journal of Function Spaces)
We introduce the notion of the C⁎-algebra-valued G-metric space. The existence and uniqueness of some fixed-point theorems for self-mappings with contractive or expansive conditions on complete C⁎-algebra-valued G-metric spaces are proved. As an application, we prove the existence and uniqueness of the solution of a type of differential equations.